2021
DOI: 10.3390/healthcare9111527
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Trait Mindfulness on Teachers’ Emotional Exhaustion: The Chain Mediating Role of Psychological Capital and Job Engagement

Abstract: Emotional exhaustion has become an important occupational health problem faced by teachers, and it has seriously affected their mental health. It is necessary to pay attention to the factors that affect emotional exhaustion. In this study, 815 frontline university faculty were selected as subjects to explore the relationship between trait mindfulness and emotional exhaustion and the role of psychological capital and work engagement in this relation, using the trait mindfulness, psychological capital, work enga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
3
5
0
Order By: Relevance
“…Our study extends this line of research by adding job crafting to the work outcomes of trait mindfulness. The mediating role of resilience in the mindfulness-job crafting relationship is in line with prior findings suggesting the mediating effect of psychological capital (i.e., hope, efficacy, resilience, and optimism) on the relationship between mindfulness and well-being (Bi & Ye, 2021 ; Roche et al, 2014 ). Thus, our findings confirmed that resilience is a key psychological resource transmitting the positive effect of trait mindfulness on work outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Our study extends this line of research by adding job crafting to the work outcomes of trait mindfulness. The mediating role of resilience in the mindfulness-job crafting relationship is in line with prior findings suggesting the mediating effect of psychological capital (i.e., hope, efficacy, resilience, and optimism) on the relationship between mindfulness and well-being (Bi & Ye, 2021 ; Roche et al, 2014 ). Thus, our findings confirmed that resilience is a key psychological resource transmitting the positive effect of trait mindfulness on work outcomes.…”
Section: Discussionsupporting
confidence: 89%
“…Mindfulness, characterized by present-moment awareness, non-judgmental observation of thoughts and emotions, and a compassionate stance toward experiences, emerged as a crucial link between psychological capital and burnout ( Kabat-Zinn, 1994 ; Roeser et al, 2013 ). This aligns with theoretical assertions that higher psychological capital endows individuals with the resources necessary to engage effectively in mindfulness practices, consequently reducing burnout tendencies ( Roche et al, 2014 ; Bi and Ye, 2021 ).…”
Section: Discussionsupporting
confidence: 85%
“…Finally, it was revealed that teacher mindfulness acted as a mediator between psychological capital and teacher burnout. This finding resonates profoundly with established theoretical frameworks and empirical evidence, illuminating the pivotal role mindfulness plays in mitigating the adverse effects of burnout by mediating the influence of psychological capital ( Roche et al, 2014 ; Bi and Ye, 2021 ). Mindfulness, characterized by present-moment awareness, non-judgmental observation of thoughts and emotions, and a compassionate stance toward experiences, emerged as a crucial link between psychological capital and burnout ( Kabat-Zinn, 1994 ; Roeser et al, 2013 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The COVID-19 pandemic has put forward new job demands and challenges for college teachers, which has a negative impact on the well-being of college teachers [ 8 , 9 ]. With the connotative development and transformation of Chinese education, college teachers shoulder arduous missions and expectations, which bring them great challenges and pressures, and may aggravate their emotional exhaustion (EE) [ 10 , 11 ]. Chinese college teachers also faced new changes and challenges during the COVID-19 pandemic [ 12 ], thus impeding the sustainable development of their well-being (WB).…”
Section: Introductionmentioning
confidence: 99%